PENINGKATAN KETERAMPILAN UMKM MELALUI PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA ANGKRINGAN - Rivara Pascha Utama; Prisila Damayanty; Aldi Pratama Putra; Hestianisari Hestianisari; Marlina Marlina; Rofina Masrin; Djunaidy Djunaidy (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
UMKM are widespread in Indonesia, especially in Jakarta. However, currently UMKM cannot be separated from a number of stimulus programs that have been launched by the government since the beginning of the Covid-19 pandemic that hit Indonesia. The number of UMKM has increased from year to year, but only a few UMKM have experienced developments in terms of their financial performance. This is because UMKM still have little knowledge in the process of recording accounting and low awareness of the importance of accounting information in the business world. Therefore, community service activities in the form of simple accounting introduction training for UMKM are still very much needed. Financial Management is an important aspect for the progress of UMKM. Financial management can be done through accounting. Accounting is a systematic process to produce financial information that can be used for decision making for its users. The use of accounting can support the progress of UMKM, especially in terms of finance. Based on the above, the service method used is simple accounting assistance for UMKM.